[Deuel and Chase Halls] (1950)
On front: "Looking N.W. across Cuesta Avenue at back portions of Deuel Dorm on left and Chase Hall on right." On back: "Dormitory Row - looking northwest at Deuel and Chase Halls (ca. 1950)"